Internet of Things Based Temperature and pH Stabilization Control System in The Pome Biodigester Fermentation Process at PLTBg - Mustofa; Dewi, Tresna; Bow, Yohandri (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2025)
The Government of Indonesia is striving to reduce dependence on fossil fuels by increasing the use of renewable energy (RE), with a target of achieving 23% by 2025. Biogas Power Plants (PLTBg) are one of the solutions that utilize palm oil mill effluent (POME) to produce biogas through anaerobic fermentation. The currently operating systems face problems and challenges in monitoring and operating mesophilic digesters, particularly covered lagoon types, which are managed conventionally, resulting in frequent drops in temperature and pH levels. To address these issues, automation was implemented in the temperature and pH control systems, with the expectation of increasing biogas production. This study adopted an approach that involved recording temperature and pH data, analyzing their upper and lower thresholds, and developing a laboratory-scale model that simulates industrial conditions. This model was equipped with a temperature and pH control system, along with monitoring and control coding. In the laboratory-scale POME digester prototype using actual POME liquid as the test medium, it was demonstrated that temperature and pH could be effectively monitored and controlled by automatically regulating the POME pump motors. The study results show that temperature control was maintained within the range of 38–41 °C, and pH control within the range of 6.5–8. The temperature drop from 40 °C to 35 °C occurred over 274 minutes. The temperature control response time was 5.6 seconds. The pH decrease rate due to the addition of fresh POME was 2.04, with a pH control response time of 8.5 seconds.